PRESUPPOSITION IN LINGUISTICS: FROM THE TRADITIONAL SEMANTIC-LOGICAL PARADIGM TO THE MODERN PRAGMATIC-COGNITIVE APPROACH - Sotvoldieva Muyassar Makhammatobbosovna (International Journal of Literature and Language Studies, 2026)
This article examines the evolution of presupposition studies in linguistics from the traditional semantic-logical paradigm to the modern pragmatic-cognitive and discourse-oriented approach. The traditional approach, rooted in the work of G. Frege, P.Strawson, and N.Chomsky, treats presupposition as a logical condition operating at the level of the isolated sentence. The modern approach, developed within pragmatics, cognitive linguistics, and discourse analysis by scholars such as P.Grice, G.Yule, and S.Levinson, and extended in Uzbek linguistics by A.Nurmonov, U.Rahimov and N.Mahmudov treats presupposition as a text- and discourse-level phenomenon shaped by context, communicative intention, and the cognitive knowledge shared by speaker and listener. Drawing on comparative textual evidence from Abdulla Kahhor's short prose and Ernest Hemingway's fiction, the article identifies four discourse functions of presupposition — securing textual coherence, enriching context, revealing character, and economizing information — and proposes a integrative model situating presupposition at the intersection of cognitive, pragmatic, social, and textual processes. The findings support the conclusion that presupposition constitutes not merely a logical or grammatical category but a communicative-pragmatic mechanism of central importance to literary discourse.